Ріст та біосинтетична активність Grifola frondosa (Dicks: Fr.) S.F. Gray та Schizophyllum commune Fr. (Basidiomycota) в глибинній культурі - Ліновецька, В.М.; Бухало, А.С. (Інститут ботаніки ім. М.Г. Холодного НАН України, 2008)
Представлены результаты исследования роста и биосинтетической активности съедобных лекарственных высших базидиомицетов Grifola frondosa (Dicks: Fr.) S.F. Gray и Schizophyllum commune Fr. из коллекции шляпочных грибов Института ботаники им. Н.Г. Холодного НАН Украины в условиях глубинного культивирования. Установлено, что для продукции биомассы лучшими источниками азота являются NH4NO3 и пептон, а углерода — глюкоза. Для дальнейших микологических и биотехнологических исследований отобраны перспективные штаммы с высоким уровнем биосинтетической активности: G. frondosa 332 и S. commune 1760. Для получения биомассы и экзополисахаридов рекомендованы комп лексные питательные среды с пептоном либо мелясой и кукурузным экстрактом для G. frondosa 332 и S. commune 1760, соответственно. The growth and biosynthetic activity of edible, medicinal mushrooms Grifola frondosa (Dicks: Fr.) S.F. Gray and Schizophyllum commune Fr. from the Collection of Fungal Cultures of the M.G. Kholodny Institute of Botany NASU (Kyiv) were investigated under submerged cultivation. The most favorable for the biomass production of the investigated strains were NH4NO3 and peptone as sources of nitrogen, and glucose as a source of carbon. Strains G. frondosa 332 and S. commune 1760 with high levels of biosynthetic activities were selected for following investigation as the biotechnological application. For biomass and exopolysaccharides production, nutritional complex mediums with peptone or molasses and with corn extract were selected for strains G. frondosa 332 and S. commune 1760, accordingly.